Semi -annual oscillation of constant pressure surfaces (1000-100 mb) in the northern hemisphere - ASNANI , G. C.; VERMA, R. K. (MAUSAM, 1975)
Monthly mean values at about 250 stations in the northern hemisphere were analysed for the study of semi-annual pressure oscillation at sea level and at 850, 700, 500, 300, 200 and 1oo mb levels. It is found that at all levels and at all longitudes, the amplitudes are smallest in the equatorial latitudes and largest in sub-tropical or higher latitudes. In the vertical, the amplitudes generally increase upwards upto about 200 mb level. There is a surface of phase reversal or sharp phase shift which slopes equatorwards with increase of height. Below this surface maximum occurs towards the end of April and October, above this surface, the maximum occurs towards the end of January and July. The oscillation is studied in some detail for the Indian region.